Robinson Crusoe - Defoe, Daniel (Hong Kong : Oxford university press, 2005)
Robinson Crusoe, written by Daniel Defoe, is the tale of an Englishman who is shipwrecked on a deserted island for 28 years. The novel follows Crusoe's journey of survival, resourcefulness, and isolation as he learns to adapt to his new environment. After being stranded, Crusoe builds shelter, grows food, and manufactures tools. His solitary existence is interrupted by the arrival of a native man, whom Crusoe names Friday. The two form a bond and work together to defend the island from intruders. Eventually, Crusoe is rescued and returns to England. The novel explores themes of adventure, self-reliance, and human resilience, offering a reflection on human nature and the struggle for survival in the face of adversity.
Keywords: English : Novel